2002
DOI: 10.1073/pnas.232444199
|View full text |Cite
|
Sign up to set email alerts
|

Pineal expression-promoting element (PIPE), a cis- acting element, directs pineal-specific gene expression in zebrafish

Abstract: The pineal gland, sharing morphological and biochemical similarities with the retina, plays a unique and central role in the photoneuroendocrine system. The unique development of the pineal gland is directed by a specific combination of the expressed genes, but little is known about the regulatory mechanism underlying the pineal-specific gene expression. We isolated a 1.1-kbp fragment upstream of the zebrafish exo-rhodopsin (exorh) gene, which is expressed specifically in the pineal gland. Transgenic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…The pineal opsin protein Exorh is expressed in pineal photoreceptors from early embryogenesis to adulthood and is thus an excellent candidate to be mediating these light responses [5,38,60]. Consistent with this, the action spectrum of acute melatonin suppression in isolated adult pineal organs suggests that Exorh is one of several opsins involved in this process [65].…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…The pineal opsin protein Exorh is expressed in pineal photoreceptors from early embryogenesis to adulthood and is thus an excellent candidate to be mediating these light responses [5,38,60]. Consistent with this, the action spectrum of acute melatonin suppression in isolated adult pineal organs suggests that Exorh is one of several opsins involved in this process [65].…”
Section: Introductionmentioning
confidence: 68%
“…The exorh gene is expressed in pineal photoreceptors from approximately 18 hours post fertilization (hpf) to adulthood [5,19,38,60]. Vuilleumier and colleagues recently reported that exorh is expressed with a daily rhythm, with higher expression during the dark phase of the circadian cycle [60].…”
Section: Results Exorh Transcription Is Rhythmicmentioning
confidence: 99%
See 3 more Smart Citations